RELEVANSI MAKNA ISTIHYA DALAM ALQURAN SURAT AL-QOSHASH AYAT 25 PERSPEKTIF PENDIDIKAN ISLAM - sirait, robin (Jurnal Generasi Tarbiyah: Jurnal Pendidikan Islam, 2023)
The meaning of istihya is a shy attitude that does not tease the opposite sex due to the obligation to maintain honor. Acts of shame and embarrassment to meet the opposite sex but still have to meet so that you lower your eyes when talking or cover your face with a cloth. Also shown with a gait that does not make or attract the attention of the opposite sex, as well as a style of dress that is full of manners. While the purpose of this article is to find out the meaning of istihya in surah Al-Qashash verse 25 in Islamic Education. This article uses qualitative research methods. With this method the researcher collects data from various reference sources and different literature so that the researcher can conclude about the Relevance of the Meaning of Istihyah in the Al-Quran Surah Al-Qoshash Verse 25 The Perspective of Islamic Education. The purpose of this article is made in order to understand the meaning of Istihyah contained in Surah Al-Qoshash from the perspective of Islamic Education.